The method of anisotropy of magnetic susceptibility: theory and applications. A case study from the Rhodope massif - ZANANIRI, I. (Bulletin of the Geological Society of Greece, 2001)
The anisotropy of magnetic susceptibility is a physical property of the rocks widely used in petrofabric studies and other applications. It is based on the measurement of low-field magnetic susceptibility in different directions along the sample. From this process several scalar properties arise, defining the magnitude and symmetry of the AMS ellipsoid, along with the magnetic foliation and lineation, namely the magnetic fabric. A case study is presented, dealing with the deformation of the Mont-Louis-Andorra pluton. Finally, the method was applied in Tertiary magmatic rocks from the Rhodope Massif, revealing their magnetic character and internal structures.